Morphophysiological responses of Billbergia zebrina Lindl. (Bromeliaceae) in function of types and concentrations of carbohydrates during conventional in vitro culture - Santos, Elizangela Rodrigues; Martins, João Paulo Rodrigues; Rodrigues, Luiz Carlos de Almeida; Gontijo, Andreia Barcelos Passos Lima; Falqueto, Antelmo Ralph (Ornamental Horticulture (Campinas), 2020)
Abstract When propagated in vitro, explants receive all the nutrients needed for their growth, including carbohydrates, from the culture medium. However, it is not well understood how the type and concentration of carbohydrates can affect the functioning of the photosynthetic apparatus (particularly photosystem II) of these plants. The aim was to assess the morphophysiological responses of Billbergia zebrina plants in function of sources and concentrations of carbohydrates during in vitro culture. Side shoots of plants previously established in vitro were individualized and transferred to a culture medium containing fructose, glucose or sucrose in four concentrations (0, 15, 30 or 45 g L−1). After growth for 55 days, the chlorophyll a fluorescence transient, leaf anatomy and growth were analyzed. The concentration and type of carbohydrate employed during in vitro culture did not decrease the photosynthetic apparatus performance. However, concentrations above 30 g L−1 led to anatomical modifications, revealing some degree of stress suffered by the plants. When grown in concentrations of 15 and 30 g L−1, irrespective of the carbohydrate used, the plants presented greater stomatal density. The supplementation of the culture medium with monosaccharides caused alterations in the development of the xylem vessels, such as increased number and diameter, allowing adjustment to the microenvironmental conditions. The in vitro conditions influenced the photosynthetic and anatomical responses of plants. The concentration interval from 15 to 30 g L−1 sucrose had a better effect by not causing large changes in the performance of the photosynthetic apparatus and anatomy of plants. Resumo Quando propagados in vitro, os explantes recebem todos os nutrientes necessários para o seu crescimento, incluindo carboidratos do meio de cultura. No entanto, ainda não se sabe como o tipo e a concentração de carboidratos pode afetar o funcionamento do aparato fotossintético (particularmente o fotossistema II) dessas plantas. O objetivo foi avaliar as respostas morfofisiológicas de plantas de Billbergia zebrina em função das fontes e concentrações de carboidratos durante o cultivo in vitro. Brotos laterais das plantas previamente estabelecidos in vitro foram individualizados e transferidos para um meio de cultura contendo frutose, glicose ou sacarose em quatro concentrações (0, 15, 30 ou 45 g L−1). Após 55 dias de cultivo foram analisadas a fluorescência transiente da clorofila a, anatomia foliar e crescimento. A concentração e tipo de carboidrato empregados durante a cultivo in vitro não diminuíram o desempenho do aparelho fotossintético. Entretanto, concentrações acima de 30 g L−1 levaram a modificações anatômicas, revelando um grau de estresse sofrido pelas plantas. Quando cultivadas nas concentrações de 15 e 30 g L−1, independentemente do carboidrato utilizado, as plantas apresentaram maior densidade estomática. A suplementação da cultura média com monossacarídeos causou alterações no desenvolvimento dos vasos xilemáticos, como aumento do número e diâmetro, permitindo o ajuste das condições microambientais. As condições in vitro influenciaram as respostas fotossintéticas e anatômicas das plantas. O intervalo de concentração de 15 a 30 g L−1 de sacarose teve melhor efeito por não causar grandes alterações no desempenho do aparato fotossintético e na anatomia das plantas.